Force Dynamics Systems in Iraqi EFL Sixth Secondary School’s Literature Passage "The Canary" - Faisal , Wafaa Mokhlos; Alwan , Abdullah Abbas (International Journal on Integrated Education, 2025)
This research utilizes a cognitive linguistic framework to examine the Force Dynamics system in Katherine Mansfield's short novel The Canary.  Inspired by Leonard Talmy's theory of Force Dynamics (1988, 2000), the work investigates how the linguistic and mental framework of the story captures interactions between agonists and antagonists.  Across physical, psychological, and social spheres, the study notes trends of force interaction including causation, enabling, hindrance, letting, and resistance.  Especially in its depiction of loneliness, bereavement, and the anthropomorphized interaction between the narrator and her canary, these dynamics offer insight into the underlying cognitive and emotional structures of the story.  The research comes to the conclusion that force dynamics significantly shapes narrative meaning and provides fresh ideas on how conceptual structures guide literary interpretation.